2020
DOI: 10.3390/polym12040909
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Hybrid Carbonaceous Fillers of Carbon Fibers and Reduced Graphene Oxides on Enhanced Heat-Dissipation Capability of Polymer Composites

Abstract: In this study, we investigated the synergistic effects of thermally conductive hybrid carbonaceous fillers of mesophase pitch-based carbon fibers (MPCFs) and reduced graphene oxides (rGOs) on the thermal conductivity of polymer matrix composites. Micro-sized MPCFs with different lengths (50 μm, 200 μm, and 6 mm) and nano-sized rGOs were used as the thermally conductive fillers used for the preparation of the heat-dissipation polymer composites. For all MPCF fillers with a different length, the thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of carbon fillers and their geometry on the heating properties of composites was also studied in [24]. In addition, synergistic effects were obtained when using hybrid carbon fillers [25][26][27]. As mentioned above, the distribution of the filler has a significant influence on the electrophysical properties.…”
Section: Introductionmentioning
confidence: 99%